Age-Specific Incidence of Melanoma in the United States - Paulson, Kelly G; Gupta, Deepti; Kim, Teresa S; Veatch, Joshua R; Byrd, David R; Bhatia, Shailender; Wojcik, Katherine; Chapuis, Aude G; Thompson, John A; Madeleine, Margaret M; Gardner, Jennifer M (JAMA dermatology (Chicago, Ill.), 2020)
Melanoma is epidemiologically linked to UV exposure, particularly childhood sunburn. Public health campaigns are increasing sun-protective behavior in the United States, but the effect on melanoma incidence is unknown. To examine the incidence of melanoma in the United States and whether any age-specific differences are present. Observational, population-based registry data were extracted on July 3, 2018, from the combined National Program of Cancer Registries-Surveillance Epidemiology and End Results United States Cancer Statistics database for 2001-2015. Deidentified data for 988 103 cases of invasive melanoma, with International Classification of Diseases for Oncology histologic categorization codes 8720 to 8790, were used for analysis. Data analysis was performed from July 1, 2018, to March 1, 2019. The annual rates of melanoma in pediatric, adolescent, young adult, and adult age groups were determined. Analyses were stratified by sex, and incidence rates were age-adjusted to the 2000 US standard population. Annual percentage change (APC) in incidence rate was calculated over the most recent decade for which data were available (2006-2015) using the weighted least squares method. In 2015, 83 362 cases of invasive melanoma were reported in the United States, including 67 in children younger than 10 years, 251 in adolescents (10-19 years), and 1973 in young adults (20-29 years). Between 2006 and 2015, the overall incidence rate increased from 200.1 to 229.1 cases per million person-years. In adults aged 40 years or older, melanoma rates increased by an APC of 1.8% in both men (95% CI, 1.4%-2.1%) and women (95% CI, 1.4%-2.2%). In contrast, clinically and statistically significant decreases were seen in melanoma incidence for adolescents and young adults. Specifically, incidence rates decreased by an APC of -4.4% for male adolescents (95% CI, -1.7% to -7.0%), -5.4% for female adolescents (95% CI, -3.3% to -7.4%), -3.7% for male young adults (95% CI, -2.5% to -4.8%), and -3.6% for female young adults (95% CI, -2.8% to -4.5%). Data on skin pigmentation and sun protection history were unavailable; similar trends were observed with data limited to non-Hispanic whites. Young adult women appeared to have twice the risk of melanoma as young adult men. The incidence of invasive melanoma in the United States appeared to decrease in adolescents and young adults from 2006 to 2015, and this finding contrasted with increases in older populations. These incidence trends suggest that public health efforts may be favorably influencing melanoma incidence in the United States.